Factores familiares, económicos, sociales y culturales que influyen en la trata infantil con fines de mendicidad en el cantón de Otavalo. - Pazmiño, Christian P. (2021)
This research work responds to the problematic situation regarding child trafficking due to various factors such as social, economic, family and cultural, violating the rights of children and adolescents in the Otavalo canton, therefore, the question of the problem was: Are there factors family, economic, social and cultural factors that influence child trafficking for the purpose of begging in the canton of Otavalo ?, the idea to defend is: In the canton of Otavalo there are family, economic, social and cultural factors that influence child trafficking for begging. The general objective is to analyze the family, social and cultural factors that influence child trafficking for the purpose of begging in the canton of Otavalo, the methodology used: research approach to be applied: qualitative, as well as the type of research: theoretical mixed -sociological, together with the methods: analytical-synthetic, the technique is the interview and documentary review; The research instruments are the recording, the observation and the interview script through the bibliographic recording of the reading. As conclusions, it is highlighted that there are factors such as migratory waves, poverty, lack of opportunity, xenophobia, domestic violence, ignorance, naturalization, among others. and the recommendations are to strengthen the ONGs for cooperation with the main actors in the matter of child trafficking, to have personnel specialized in the problem and to establish a mechanism for the inclusion of migrants to the country.